DESCRIPTION OF KNOWLEDGE ABOUT TOPICAL APPLICATION FLUOR (TAF) IN PARENTS OF PRIMARY SCHOOL AGE CHILDREN (Politeknik Kesehatan Kemenkes Bandung, 2020)
Introduction: Lack of information and knowledge of parents about dental caries and prevention, can be the cause of dental caries in children. Nearly 90% of school-age children worldwide suffer from dental caries. In 2018, the prevalence of caries in the 12 year age group is 72%, one of the ways that can be done to prevent dental caries is by using fluoride topically. Purpose: This study aims to determine the description of parents' knowledge of elementary school age children in Kabupaten Sumedang about Topical Fluoride Applications (TAF). Methods: This research is a descriptive study with in-dept interview method. The population of this study is the parents of elementary school age children in the village of Sumedang Regency with 15 people. Sampling is done using Total Sampling. Result: The results showed the level of knowledge of parents of elementary school age children about Fluorical Topical Application (TAF) in Sumedang Regency, on average had a good level of knowledge, as many as 9 respondents with a percentage of (60%). Respondents who have a level of knowledge of less than (14%) as many as 2 respondents. Conclusion: Most respondents have good knowledge of the benefits of Topical Application Fluor (TAF) and respondents have less knowledge of the general description of Topical Application Fluor (TAF).